Lead, mercury, and cadmium in breast milk - Kadriye Yurdakök (Hygeia Press di Corridori Marinella, 2015)
Toxic heavy metals are the major source of environmental pollution in this new millennium. Lead, mercury, and cadmium are the most common toxic heavy metals in the environment. There is no known function of these toxic heavy metals in the human body. In females, toxic heavy metals can be accumulated in maternal body before pregnancy and may be transferred to fetus through placenta and later, via breast milk. Lead previously accumulated in maternal bones can be mobilized along with calcium in order to meet increased calcium needs of the fetus in pregnant women and for the calcium needs in human milk during lactation. Human fetus and infants are susceptible to heavy metal toxicity passing through placenta and breastmilk due to rapid growth and development of organs and tissues, especially central nervous system. However most of the damage is already done by the time the infant is born. Intrauterine lead exposure can cause growth retardation, cognitive dysfunction, low IQ scores on ability tests, and low performance in school. Biological samples, such as umbilical cord blood and breast milk, and less commonly infant hair, are used for biomonitoring of intra-uterine exposure to these toxic chemicals. Although toxic metals and other pollutants may be excreted into breast milk, their effects are unknown and this topic is subject of a growing body of research. Despite the possibility of harm from environmental contaminants in breast milk, breastfeeding is still recommended as the best infant feeding method. In fact, the species-specific components present in breast milk protect infants against infections; promote immune and neurologic system development; and may decrease the risk of disease, including allergies, obesity, insulin-dependent diabetes mellitus, inflammatory bowel disease, and sudden infant death syndrome. Breastfeeding also facilitates maternal-infant attachment. The potential risk of environmental contaminants that can be transferred from mother to infant via breastfeeding can be alleviated by reducing life-long exposure since toxic chemicals accumulate long before pregnancy and released during gestation and lactation. Thus, management should aim to reduce life-long exposure through precautionary measures such as prevention of exposure to cigarette smoking, use of unleaded gasoline, and prevention of air pollution with an effect at the community level.   Proceedings of the 11th International Workshop on Neonatology and Satellite Meetings · Cagliari (Italy) · October 26th-31st, 2015 · From the womb to the adult Guest Editors: Vassilios Fanos (Cagliari, Italy), Michele Mussap (Genoa, Italy), Antonio Del Vecchio (Bari, Italy), Bo Sun (Shanghai, China), Dorret I. Boomsma (Amsterdam, the Netherlands), Gavino Faa (Cagliari, Italy), Antonio Giordano (Philadelphia, USA)